PENGARUH URIN SAPI DAN PANJANG SETEK TERHADAP PERTUMBUHAN JAMBU AIR MADU - Elfi Rahmayani; Arnis En Yulia (DINAMIKA PERTANIAN, 2020)
ABSTRACT This study aims to determine the effect of cow urine and cutting length on the growth of guava honey. This study was performed at the experimental farm of the Faculty of Agriculture, University of Riau, Pekanbaru from February to May 2019. The research used the completely randomized design (RAL) factorial. The first factor was the concentration of cow urine consisting of 25%, 50%, and 75%. The second factor was the size of the length consisting of 15 cm, 20 cm, and 25 cm. The observed parameters consisted of the day of emerging buds, number of shoots, length of shoots, number of roots, root length, and root volume. The results of the study showed that a combination of cow urine treatment with long cuttings had an unreal effect on all parameters. A single long factor of cuttings gave a noticeable effect on all parameters except for the number of roots. The single factor of cow urine gave an unreal effect to all parameters except the length of the bud. The combination of cow urine concentration was 50% and 75% with a length of 25 cm could increase the growth of honey-water seedlings. Key Words: Cow urine, Cutting length, Growth, Guava honey.